Validation of community health worker identification of maternal puerperal sepsis using a clinical diagnostic algorithm in Bangladesh and Pakistan - LeFevre, Amnesty E; Mir, Fatima; Mitra, Dipak K; Ariff, Shabina; Mohan, Diwakar; Ahmed, Imran; Sultana, Shazia; Winch, Peter J; Shakoor, Sadia; Connor, Nicholas E; Islam, Mohammad Shahidul; El-Arifeen, Shams; et al. (Journal of global health, 2021)
Puerperal sepsis (PP sepsis) is a leading cause of maternal mortality globally. The majority of maternal sepsis cases and deaths occur at home and remain undiagnosed and under-reported. In this paper, we present findings from a nested case-control study in Bangladesh and Pakistan which sought to assess the validity of community health worker (CHW) identification of PP sepsis using a clinical diagnostic algorithm with physician assessment and classification used as the gold standard. Up to 300 postpartum women were enrolled in each of the 3 sites 1) Sylhet, Bangladesh (n = 278), 2) Karachi, Pakistan (n = 278) and 3) Matiari, Pakistan (n = 300). Index cases were women with suspected PP Sepsis as diagnosed by CHWs clinical assessment of one or more of the following signs and symptoms: temperature (recorded fever ≥38.1°C, reported history of fever, lower abdominal or pelvic pain, and abnormal or foul-smelling discharge. Each case was matched with 3 control women who were diagnosed by CHWs to have no infection. Cases and controls were assessed by trained physicians using the same algorithm implemented by the CHWs. Using physician assessment as the gold standard, Kappa statistics for reliability and diagnostic validity (sensitivity and specificity) are presented with 95% CI. Sensitivity and specificity were adjusted for verification bias. The adjusted sensitivity and specificity of CHW identification of PP sepsis across all sites was 82% (Karachi: 78%, Matiari: 78%, Sylhet: 95%) and 90% (Karachi: 95%, Matiari: 85%, Sylhet: 90%) respectively. CHW-Physician agreement was highest for moderate and high fever (range across sites: K = 0.84-0.97) and lowest for lower abdominal pain (K = 0.30-0.34). The clinical signs and symptoms for other conditions were reported infrequently, however, the CHW-physician agreement was high for all symptoms except severe headache/ blurred vision (K = 0.13-0.38) and reported "lower abdominal pain without fever" (K = 0.39-0.57). In all sites, CHWs with limited training were able to identify signs and symptoms and to classify cases of PP sepsis with high validity. Integrating postpartum infection screening into existing community-based platforms and post-natal visits is a promising strategy to monitor women for PP sepsis - improving delivery of cohesive maternal and child health care in low resource settings.